2021
DOI: 10.1001/jamacardio.2021.3702
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Association Between Episodes of Atrial Fibrillation and Risk of Ischemic Stroke

Abstract: IMPORTANCEUnderstanding the temporal association between atrial fibrillation (AF) and ischemic stroke informs our understanding of the AF-stroke mechanism and treatment of paroxysmal AF.OBJECTIVE To define the temporal association between episodes of AF and stroke in patients with cardiac implantable electronic devices (CIEDs). DESIGN, SETTING, AND PARTICIPANTSIn this case-crossover study, data from a large national electronic health record database were linked with a single-vendor database of heart rhythm rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 31 publications
2
64
0
Order By: Relevance
“…A recent case-crossover study of 891 patients with ischemic stroke and intracardiac devices explored the temporal association between incidence of AF and risk of ischemic stroke. Heart rhythm 30 days pre-stroke (cases) were compared to those 91-120 days pre-stroke (controls) (31); 52 patients experienced AF episodes of 5.5 hours or more in the case period of 30 days in comparison to 14 patients in the control period -reflecting a 3.71-fold increased risk of stroke in weeks following multi-hour AF episodes (31) The risk of stroke was the highest within the first five days after an AF episode. (31).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent case-crossover study of 891 patients with ischemic stroke and intracardiac devices explored the temporal association between incidence of AF and risk of ischemic stroke. Heart rhythm 30 days pre-stroke (cases) were compared to those 91-120 days pre-stroke (controls) (31); 52 patients experienced AF episodes of 5.5 hours or more in the case period of 30 days in comparison to 14 patients in the control period -reflecting a 3.71-fold increased risk of stroke in weeks following multi-hour AF episodes (31) The risk of stroke was the highest within the first five days after an AF episode. (31).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…31 The risk of stroke was highest within the first 5 days after an AF episode. 31 While this cohort was not specific to patients with HF and most patients did not meet the threshold of AF burden, these results suggest that remote monitoring for these variables could assist in risk stratification of patients ( Fig. 4 ).…”
Section: Can Risk Stratification Identify Patients Who May Benefit Fr...mentioning
confidence: 99%
“…On the other hand, there is no consensus on the threshold of AF episode durations that are clinically relevant, especially in stroke patients ( 30 ). However, a study performed by Singer et al confirmed the direct and transient association between AF and stroke while using an AF duration threshold of 5.5 h. Furthermore, they found that AF episodes with a duration of more than 23 h were associated with the most significant increased stroke risk ( 31 ). Therefore, two discrete mHealth spot-check recordings per day using a smartphone or smartwatch should be sufficient to detect clinically relevant AF episodes.…”
Section: Discussionmentioning
confidence: 98%
“…Third, device-detected AF burden is associated with an increased risk of ischaemic stroke in patients with cardiac implanted electronic devices 15. A recent study suggested that excess stroke risk above baseline was highest within 5 days of an episode of AF of 5.5 hours or more in duration and diminished rapidly thereafter 16. It is possible that a substantial portion of ILR-detected AF may be a lower burden, shorter duration and carrying a relatively lower risk of stroke 14…”
Section: Discussionmentioning
confidence: 99%